2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24358
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Actor–Network Theory via the Engineering Sophomore Year

Abstract: The second year or sophomore year of most 4-year engineering undergraduate programs includes completion of the final fundamental math and science courses required for an engineering degree. We believe the intensive examination of this critical year in undergraduate engineering education is warranted, and advocate for a new perspective in analyzing the social and cultural environments of gateway engineering mathematics courses of the sophomore year -specifically Calculus 3 for Engineers and Differential Equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Allowing the interaction patterns of the environment to be scrutinized, potentially revealing the hidden social structure of the environment. SNA has been used in a variety of STEM environments ranging from understanding how teaching resources and pedagogies are spread and utilized, 9,25-27 perceptions of other team member interactions, 24 retention and persistence issues, 28,29 and to understand the social process of ethical design. 30 Given the body of literature demonstrating the importance of social interactions we propose that diverse individuals should be dispersed throughout the network to encourage meaningful interactions with a wide variety of people, thus warming the climate of engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Allowing the interaction patterns of the environment to be scrutinized, potentially revealing the hidden social structure of the environment. SNA has been used in a variety of STEM environments ranging from understanding how teaching resources and pedagogies are spread and utilized, 9,25-27 perceptions of other team member interactions, 24 retention and persistence issues, 28,29 and to understand the social process of ethical design. 30 Given the body of literature demonstrating the importance of social interactions we propose that diverse individuals should be dispersed throughout the network to encourage meaningful interactions with a wide variety of people, thus warming the climate of engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The data suggest that students are developing robust and diverse social networks. Several studies have shown that academic success is positively correlated with participation in the social network [10], [30]- [33]. The creation of a heterogenous social network means that students have opportunities to interact with a broad range of students.…”
Section: Discussionmentioning
confidence: 99%
“…There was no influence of ANT in the analysis and discussion. Also analyzing the educational setting at the program level, Tsai et al (2015) investigated how the sophomore-year mathematics courses (and its elements -teachers, courses, physical space, culture, etc.) translated students that interacted with them.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The authors took the time to explain the theory and many key concepts, such as the four moments of translation -problematization, interessement, enrollment and mobilization. Tsai et al (2015) used these four moments of translation to analyze how the translation process of students occurred as they interacted with the elements of the mathematics courses.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation